Human papillomavirus associated head and neck squamous cell carcinoma: Controversies and new concepts - Nuzhat Husain; Azfar Neyaz (Elsevier, 2017)
High-risk human papillomavirus (HR-HPV) is a causative agent for an increasing subset of oropharyngeal squamous cell carcinoma. HPV 16 accounts for 90% of cases. The chance for malignant transformation due to infection with high-risk HPV is proportional to the expression of the viral oncogene products E6 and E7, which inactivate p53 and retinoblastoma (Rb) tumor suppressor functions. P16 is a surrogate marker of HPV associated HNSCC and 2+/3+ expression in more than 75% cells is diagnostic. Molecular demonstration of integrated virus by in situ hybridization is specific but has low sensitivity. HPV associated oropharyngeal carcinomas classically arise in the tonsillar crypts and commonly have basaloid morphology with a prominent lymphocytic repsonse and minimal despmoplastic reaction. In situ vs invasive carcinomas may be difficult to distinguish in histology. The HPV postitivity overrides traditional prognostic indicators such as tumour grade and histological subtype. Small cell morphology carries a poorer prognosis as does marked tumour anaplasia and multinucleation. Lymph node metastasis is extensive and frequently cystic however extranodal extension, laterality or nodal sizes do not carry prognostic implications as in conventional OSCC and OPSCC. Stage IV is reserved for distant metastasis. HPV-16-positive patients had significantly reduced overall and disease-specific mortality rates and an improved 3-year overall survival (OS) and disease-free survival (DFS) compared to patients with HPV negative tumors. Surgical treatment is the main option for primary and secondary HNSCC. Targeted therapies including drugs targeting EGFR and PIK3CA and have shown some promising results. HPV pathway expressing tumors are less aggressive and may receive adequate curative intent therapy from a reduced radiation or chemotherapy dose revision. OSCC however fails to show a distinct difference between HPV associated and tobaccco associated cancer and prognostic differences do not clearly exist.